World Bank CCS Program Activities in South Africa : Results and Lessons Learned - Beck, Brendan (Elsevier, 2018)
The World Bank Group (WB) Carbon Capture and Storage Trust Fund (CCS TF) was established in 2009 to support CO2 capture and storage (CCS) capacity and knowledge building in developing countries. This support is intended to create opportunities for the WB partner countries to explore their CCS potential and, if appropriate, to facilitate the inclusion of CCS options into their low-CO2 growth strategies and policies. Nine countries were selected in Phase 1 of the CCS TF support including South Africa. CCS TF Phase 1 support for CCS in South Africa included an allocation of US$ 1.35 million and had the objective of supporting the Government of South Africa by undertaking three specific studies: 1. The development of a regulatory framework for CCS in South Africa. 2. A techno-economic review of CCS implementation in South Africa. 3. The development of a national and local public engagement plan for the South African Pilot CO2 Storage Project.